Factores de riesgo asociados a la prevalencia de malaria asintomática entre adultos de comunidades cercanas a la ciudad de Iquitos - Arista Flores, Katty Madeleine (2025)
This study evaluated risk factors associated with asymptomatic malaria among adults in communities near Iquitos: Zungarococha, Puerto Almendra, Ninarumi, and Llanchama. The sample consisted of 412 adults enrolled in a previous study conducted in 2017. The techniques used were a database review and standardized PCR and ELISA tests, and the instruments were a data collection form and a results processing form. The study found a prevalence of 10.2% of asymptomatic malaria, 4 times (16.5%) more cases of malaria were detected by PCR, 64.7% of submicroscopic cases were asymptomatic, and 97.6% of asymptomatic malaria cases were caused by Plasmodium vivax. The sociodemographic factors associated with the risk of asymptomatic malaria were living in Llanchama (OR 3.5, p<0.001, 95% CI 1.776–6.995) and being a laborer (OR 4.2, p=0.021, 95% CI 1.241–14.363). The epidemiological factors associated with the risk of asymptomatic malaria were always being in the fields or mountains at dusk or dawn (OR 3.0, p=0.025, 95% CI 1.150–7.870) and the presence of malaria cases in the home in the last 12 months (OR 4.0, p<0.001, 95% CI 1.820 – 8.930). The clinical factor associated with the risk of asymptomatic malaria was having a history of malaria (OR2.8, p<0.001, 95% CI, 1.570– 5.120). In conclusion, there is a high prevalence of asymptomatic infections in adults in communities near Iquitos. In addition, living in Llanchama, always being near the countryside or forest after sunset or sunrise, the presence of malaria cases in the home in the last year, and having a history of malaria increase the risk of asymptomatic malaria.